Pengaruh Kenaikan PPN, Celebrity Endorser terhadap Minat Daya Beli Konsumen pada Produk Skin Care dengan Kualitas Produk sebagai Variabel Moderasi - Sri Lestari Yuli Prastyatini; Arum Puspita (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this research is to determine how rising Value Added Tax (VAT), celebrity endorsers on consumer purchasing power interest in skin care products with product quality as moderation. The research was conducted on female students of the Faculty of Economics, Sarjanawiyata Tamansiswa University for the 2019-2020 period. Research data can be obtained through the distribution of questionnaires. The sample in this study was processed using the slovin formula which resulted in 173 samples. The research data was processed using SPSS with multiple linear regression and Moderate Regression Analysis (MRA). The hypothesis testing method uses a significance level of 5%. The results of this study indicate that the increase in VAT has a positive effect on consumer purchasing power. celebrity endorser has a positive effect on consumer purchasing power interest. Product quality is able to moderate the increase in VAT and celebrity endorsers on consumer purchasing power.